2019
DOI: 10.3389/fphys.2019.00521
|View full text |Cite
|
Sign up to set email alerts
|

Off-Target Effects of Clozapine-N-Oxide on the Chemosensory Reflex Are Masked by High Stress Levels

Abstract: Respiratory chemosensory circuits are implicated in several physiological and behavioral disorders ranging from sudden infant death syndrome to panic disorder. Thus, a comprehensive map of the chemosensory network would be of significant value. To delineate chemosensory neuronal populations, we have utilized pharmacogenetic Designer Receptors Exclusively Activated by Designer Drugs (DREADD) perturbations for acute neuronal perturbations in respiratory circuit mapping. Recent studies show that the biologically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 51 publications
3
29
0
Order By: Relevance
“…It is also plausible that chronic CNO administration potentiates the browning of iWAT and energy expenditure, which is beyond the scope of our acute GPCR stimulation studies. However, chronic treatment with high doses of CNO are associated with many adverse effects [62], mostly due to its back-transformation into clozapine [48], that could limit the attractiveness to such an approach. Nonetheless, these chemogenetic approaches will be invaluable tools for chronically or acutely controlling these pathways in a spatiotemporal manner.…”
Section: Discussionmentioning
confidence: 99%
“…It is also plausible that chronic CNO administration potentiates the browning of iWAT and energy expenditure, which is beyond the scope of our acute GPCR stimulation studies. However, chronic treatment with high doses of CNO are associated with many adverse effects [62], mostly due to its back-transformation into clozapine [48], that could limit the attractiveness to such an approach. Nonetheless, these chemogenetic approaches will be invaluable tools for chronically or acutely controlling these pathways in a spatiotemporal manner.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies, including one of the authors' studies 7 , showed no significant non-specific response 39 , 40 , while higher doses (e.g., 10 mg/kg) can produce side effects, at least in some cases 41 . However, as with all behavioral experiments, proper controls 31 are essential due to potential off-targeted activity of CNO and its metabolites 42 . Such controls could include administration of CNO and saline controls to animals expressing DREADDs and administration of CNO to wild-type animals or in some specific cases a comparison of ipsi-and contralateral sites of the brain that respectively do and do not express chemogenetic receptors.…”
Section: Representative Resultsmentioning
confidence: 99%
“…It was reported that 0.5 mg/kg CNO resulted in behavioral signs of seizure activity in approximately 20% of mice during fear conditioning (Garner et al, 2012 ). The high dose of CNO (10 mg/kg) also showed off-target effects (Martinez et al, 2019 ). A high dose of CNO may produce nonspecific side effects.…”
Section: Discussionmentioning
confidence: 99%